Women without Class : Girls, Race, and Identity. - Bettie, Julie, 1965- (University of California Press, 2014)
In this examination of white and Mexican-American girls coming of age in California''s Central Valley-now with a new introduction-Julie Bettie turns class theory on its head, offering new tools for understanding the ways in which identity is constructed in relationship to race, ethnicity, gender, and sexuality. Documenting the categories of subculture and style that high school students use to understand their differences, Bettie depicts the complex identity performances of contemporary girls. The title, Women Without Class, refers at once to young working-class women who have little cultural c.